Blocked stomodeal valve of the insect vector: similar mechanism of transmission in two trypanosomatid models - Volf, P; Hajmova, M; Sadlova, J; Votypka, J (International journal for parasitology, 2004)
The regurgitation of metacyclic stages from the sand fly cardia is thought to be the prevailing mechanism of Leishmania transmission. This regurgitation may result through damage of the stomodeal valve and its mechanical block by the parasites. We found this phenomenon in three sand fly-Leishmania models and also in avian trypanosomes transmitted by Culex mosquitoes. Phlebotomus duboscqi, Phlebotomus papatasi, Lutzomyia longipalpis, and Culex pipiens were membrane-fed on blood containing Leishmania major, Leishmania chagasi (syn. infantum) and an unidentified avian Trypanosoma from Trypanosoma corvi clade, respectively. Females with the late-stage infections were processed for the optical and transmission electron microscopy. Localization of the parasites and changes to the stomodeal valve were in some aspects similar in all vector-parasite pairs studied: (i) a large plug of flagellates was observed in cardia region, (ii) parasites were attached to the chitin lining of the stomodeal valve by the formation of zonal hemidesmosome-like plaques. Leishmania promastigotes were found both attached to the valve as well as unattached in the lumen of midgut. The stomodeal valve of infected sand flies was opened, its chitin lining was destroyed and the unique filamentous structures on the apical end of cylindrical cells were degraded. In the Culex-Trypanosoma model, the whole population of epimastigotes was found in close contact with the chitin lining, and degenerative changes of the valve were less pronounced. We suggest that the phenomenon involving a blocked valve facilitating the regurgitation of parasites into the vertebrate host may occur generally in heteroxenous trypanosomatids transmitted by the bite of nematoceran Diptera.
Keywords: Chitin; Microscopy, Electron; Insect Vectors; Phlebotomus; trypanozomiáza; Female; leishmanióza kožní; zvířata; Culex; Trypanosomiasis; Leishmaniasis, Cutaneous; ženské pohlaví; leishmanióza; hmyz - vektory; Leishmaniasis; elektronová mikroskopie; Animals; Psychodidae; chitin